Plasmid replication-associated single-strand-specific methyltransferases. Issue 22 (3rd December 2020) - Fomenkov, Alexey; Sun, Zhiyi; Murray, Iain A; Ruse, Cristian; McClung, Colleen; Yamaichi, Yoshiharu; Raleigh, Elisabeth A; Roberts, Richard J
Abstract: Analysis of genomic DNA from pathogenic strains of Burkholderia cenocepacia J2315 and Escherichia coli O104:H4 revealed the presence of two unusual MTase genes. Both are plasmid-borne ORFs, carried by pBCA072 for B. cenocepacia J2315 and pESBL for E. coli O104:H4. Pacific Biosciences SMRT sequencing was used to investigate DNA methyltransferases M.BceJIII and M.EcoGIX, using artificial constructs. Mating properties of engineered pESBL derivatives were also investigated. Both MTases yield promiscuous m6A modification of single strands, in the context SAY (where S = C or G and Y = C or T). Strikingly, this methylation is asymmetric in vivo, detected almost exclusively on one DNA strand, and is incomplete: typically, around 40% of susceptible motifs are modified. Genetic and biochemical studies suggest that enzyme action depends on replication mode: DNA Polymerase I (PolI)-dependent ColE1 and p15A origins support asymmetric modification, while the PolI-independent pSC101 origin does not. An MTase-PolI complex may enable discrimination of PolI-dependent and independent plasmid origins. M.EcoGIX helps to establish pESBL in new hosts by blocking the action of restriction enzymes, in an orientation-dependent fashion. Expression and action appear to occur on the entering single strand in the recipient, early in conjugal transfer, until lagging-strand replication creates the double-stranded form.